A multicentre comparative prospective blinded analysis of EUS and MRI for screening of pancreatic cancer in high-risk individuals. Issue 9 (18th May 2015) - Harinck, F; Konings, I C A W; Kluijt, I; Poley, J W; van Hooft, J E; van Dullemen, H M; Nio, C Y; Krak, N C; Hermans, J J; Aalfs, C M; Wagner, A; Sijmons, R H; et al.
Abstract : Objective: Endoscopic ultrasonography (EUS) and MRI are promising tests to detect precursors and early-stage pancreatic ductal adenocarcinoma (PDAC) in high-risk individuals (HRIs). It is unclear which screening technique is to be preferred. We aimed to compare the efficacy of EUS and MRI in their ability to detect clinically relevant lesions in HRI. Design: Multicentre prospective study. The results of 139 asymptomatic HRI (>10-fold increased risk) undergoing first-time screening by EUS and MRI are described. Clinically relevant lesions were defined as solid lesions, main duct intraductal papillary mucinous neoplasms and cysts ≥10 mm. Results were compared in a blinded, independent fashion. Results: Two solid lesions (mean size 9 mm) and nine cysts ≥10 mm (mean size 17 mm) were detected in nine HRI (6%). Both solid lesions were detected by EUS only and proved to be a stage I PDAC and a multifocal pancreatic intraepithelial neoplasia 2. Of the nine cysts ≥10 mm, six were detected by both imaging techniques and three were detected by MRI only. The agreement between EUS and MRI for the detection of clinically relevant lesions was 55%. Of these clinically relevant lesions detected by both techniques, there was a good agreement for location and size. Conclusions: EUS and/or MRI detected clinically relevant pancreatic lesions in 6% of HRI. Both imaging techniques were complementary rather than interchangeable: contrary to EUS, MRI was found to be very sensitive for the detection of cystic lesions of any size; MRI, however, might have some important limitations with regard to the timely detection of solid lesions.